Association of anaemia and mortality in patients with acute pulmonary embolism - Jiménez, David; Escobar, Carlos; Martí, David; Díaz, Gema; César, Jesús; García-Avello, Ángel; Sueiro, Antonio; Yusen, Roger D. (Thrombosis and Haemostasis, 2009)
This study aimed to evaluate the relationship between anaemia and pulmonary embolism (PE) prognosis. We analysed a cohort of 764 patients with acute PE referred to a single center for diagnosis and management. Patients were divided into groups by quartiles of haemoglobin (Hb): Hb < 11.7 g/dl; Hb 11.7 to 12.9 g/dl; Hb 13.0 to 14.1 g/dl; Hb > 14.1 g/dl. Patients had a mean Hb of 12.9 g/dl, and values ranged from to 4.3 to 19.5 g/dl. Lower Hb was associated with recent bleeding, an impaired haemodynamic profile and higher creatinine. Patients in the lower Hb quartiles more commonly had female gender (p < 0.001), a diagnosis of cancer (p < 0.001), and an indication for an inferior vena cava (IVC) filter (p < 0.002), compared to patients in the higher Hb quartiles. Patients in higher Hb quartiles had higher survival at three months (75%, 86%, 90% and 91% for lowest to highest quartiles, respectively). On multivariate analysis, adjusting for known PE prognostic factors, low Hb proved to be an independent predictor of mortality (hazard ratio [HR] 1.16, 95% confidence interval [CI] 1.05 to 1.28 for each decrease of 1 g/dl). Hb level remained an independent predictor of all-cause mortality when cancer patients were excluded from the analysis (adjusted HR 0.81; 95% CI, 0.66 to 0.99; p = 0.04). Moreover, patients with anaemia showed a higher risk of fatal PE (unadjusted HR 1.19, 95% CI 1.04 to 1.37). In conclusion, in patients with acute symptomatic PE, anaemia severity is associated with worsened survival.
Keywords: Clinical studies; lung; pulmonary embolism; anaemia; prognosis